BİR ÜNİVERSİTE HASTANESİNDE YATAN TİP 2 DİYABETLİ HASTALARIN TEDAVİYE UYUM DÜZEYLERİNİN VE ETKİLEYEN FAKTÖRLERİN İNCELENMESİ - MEMİŞ, DURSUN (Fırat Üniveristesi, 2022)
Diyabet, ülkemizde ve dünya çapında önem arz eden bir sağlık sorunudur. Bu çalışmada amaç; Fırat Üniversitesi Tıp Fakültesi Hastanesinde yatmakta olan ve tip 2 diyabet tedavisi alan hastaların tedaviye uyum düzeylerinin ve etkileyen faktörlerin incelenmesidir. Kesitsel tipte olan bu araştırmada Fırat Üniversitesi Tıp Fakültesi Hastanesi servislerinde yatmakta olan 215 tip 2 diyabet tanısı almış hastalara, gerekli izinler ve etik kurul kararı alındıktan sonra anket uygulanmıştır. Anketin ilk kısmı sosyodemografik soruları ve hastalığa yönelik soruları içermektedir. İkinci kısım diyabette komplikasyonlara ilişkin risk algı ölçeği, üçüncü kısım tip 2 diyabet tedaviye uyum ölçeği ve dördüncü bölüm diyabette engeller ölçeğinden oluşmaktadır. Çalışmaya dahil edilen hastaların yaş ortalaması 59,5±8,7 (min=39-maks=81), %53'ü kadın olup %75,8'i evlidir. Hastaların %20,5'inin tedaviye uyumunun iyi olduğu, %73,5'inin orta olduğu ve %6'sının kötü olduğu görülmüştür. Ortaokul ve altında eğitim durumuna sahip olanların toplam tedaviye uyum ölçeği puanı, lise ve üzeri olan eğitim durumuna sahip gruba göre anlamlı şekilde yüksekti (p <0,001). Ekonomik durum arttıkça tedaviye uyum ölçeği toplam puanı azalmaktaydı (p<0,001). İlde yaşayan hastalarda tedaviye uyum ölçeği toplam puanı ilçe/köyde yaşayanlara göre anlamlı şekilde düşüktü (p<0,001). Sigara kullanma durumu arasında tedaviye uyum ölçeği toplam puan açısında anlamlı farklılık görülmüştür (p=0,011). Hastalığının getirdiği masrafları karşılamada zorluk çekenlerin (p=0,031), egzersiz yapmayanların (p<0,001), diyabet eğitimi almamış olanların (p<0,001) ve komplikasyon gelişmiş olanların (p=0,002) tedaviye uyum puanlarının anlamlı şekilde yüksek olduğu bulunmuştur. Sonuç olarak hastaların tedaviye uyumunun genel olarak orta düzeyde olduğu ve uyumda eksiklikler olduğu görülmüştür. Hastaları hastalık hakkında eğitmek ve sosyoekonomik durumlarını iyileştirmek tedaviye uyumu arttırabilir. Anahtar kelimeler: Diyabet, tedaviye uyum, risk algısı, diyabet engelleri

Diabetes is an important health problem in our country and around the world. The aim of this study is to investigate treatment adherence levels and influencing factors in patients hospitalized in the hospital of Fırat University Faculty of Medicine and treated for type 2 diabetes. In this cross-sectional study, a questionnaire was administered to 215 patients diagnosed with type 2 diabetes who were hospitalized in the wards of Fırat University Faculty of Medicine Hospital after obtaining the necessary permissions and the ethics committee's decision. The first part of the questionnaire contains socio-demographic questions and questions about the disease. The second part consists of the risk perception scale for complications in diabetes, the third part consists of the type 2 diabetes treatment adherence scale, and the fourth part consists of the diabetes barriers scale. The mean age of patients included in the study was 59.5±8.7 (min=39-max=81), 53% were women and 75.8% were married. It was observed that 20.5% of patients had good adherence to treatment, 73.5% had moderate adherence and 6% had poor adherence. The total treatment adherence scale score of those who had secondary and lower educational status was significantly higher than in the group who had high school and above educational status (p<0.001). As the economic status increased, the total treatment adherence scale score decreased (p<0.001). The total score of the treatment adherence scale was significantly lower in patients who lived in the province than in those who lived in the district/village (p<0.001). There was a significant difference between the smoking status in terms of the total score of the adherence to treatment scale (p=0.011). Those who had difficulty paying for their disease (p=0.031), those who did not exercise (p<0.001), those who did not receive diabetes education (p<0.001), and those who developed complications (p=0.002) were found to have significantly higher treatment adherence scores. As a result, it was seen that patients' treatment adherence was generally at a moderate level and there were deficits in adherence. Educating patients about the disease and improving their socioeconomic status could increase treatment adherence. Keywords: Diabetes, treatment adherence, risk perception, diabetes barriers
Investigation of treatment adherence levels and influencing factors of patients with TYPE 2 diabetes hospitalized in A university hospital
Keywords: Halk Sağlığı